PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP PENGHINDARAN PAJAK SEBELUM DAN SAAT PANDEMI COVID-19 - Swandhana, Jeremy; Santoso, Eko Budi (Media Akuntansi dan Perpajakan Indonesia, 2023)
This study aims to examine the effect of Profitability and solvability on tax avoidance in LQ-45 companies before and during the Covid19 pandemic. The observations used a total of 152 as different test observations and 75 as influence test observations before Covid-19 and 72 as influence test observations during Covid-19, these observations were carried out using the purposive sampling method for sampling and data. The analysis used is multiple linear regression analysis and independent sample t-test analysis. The independent variables used are profitability and solvency then the dependent variable is tax avoidance with size and PPE control variables while for the independent sample t-test using tax avoidance variables. The results of the F test show that the regression model is feasible to use, while the results of the t-test analysis show that the profitability variable has a significant positive effect on tax evasion on both phenomena before and during Covid-19, while solvency has no effect on both phenomena before and during Covid-19, for test results difference shows F which is not significant, meaning that there is no difference before and during Covid-19. So it can be concluded that profitability affects tax evasion in a positive direction and solvency does not affect tax evasion with different test results which state that there is no difference in behavior tax evasion before and during Covid–19.